How do low-income enrollees in the affordable care act marketplaces respond to cost sharing? - Kurt Lavetti; Thomas C. DeLeire; Nicolas R. Ziebarth (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
The Affordable Care Act requires insurers to offer cost sharing reductions (CSRs) to low-income consumers on the Marketplaces. We link 2013-2015 All-Payer Claims Data to 2004-2013 administrative hospital discharge data from Utah and exploit policy-driven differences in the actuarial value of CSR plans that are solely determined by income. This allows us to examine the effect of cost sharing on medical spending among low-income individuals. We find that enrollees facing lower levels of cost sharing have higher levels of health care spending, controlling for past health care use. We estimate demand elasticities of total health care spending among this low-income population of approximately -0.12, suggesting that demand-side price mechanisms in health insurance design work similarly for low-income and higher-income individuals. We also find that cost sharing subsidies substantially lower out-of-pocket medical care spending, showing that the CSR program is a key mechanism for making health care affordable to low-income individuals.
Keywords: H24; H41; H43; H51; I11; I18; J32; J33; J68; 330; demand elasticities; health insurance; moral hazard; ACA; marketplaces; AV-variants; low-value care; lifestyle drugs; value-based CSRs; Utah